Development & Characterization of Fast Dissolving Tablet of Vanoprazone - Amit Kumar Tiwari; Sangamnath B; Anugrah; Maharaja; Mahibub M; Vinayaka; Vishwaradhya (International Journal of Pharmacy and Analytical Research, 2026)
The present study focuses on the formulation and evaluation of fast dissolving tablets (FDTs) of Vonoprazan using the direct compression method. Various superdisintegrants Sodium Starch Glycolate (SSG), Crospovidone, and Croscarmellose Sodium were incorporated at different concentrations to optimize disintegration and drug release. Select formulations included subliming agents (camphor or menthol) and were subjected to vacuum drying to enhance porosity and dissolution efficiency. All tablets were assessed for pre- and post-compression parameters including thickness, weight variation, hardness, friability, wetting time, dispersion time, disintegration time, drug content, and in vitro release. Among the formulations, VFDT6 (SSG-based) demonstrated superior performance with rapid disintegration, high drug content, low friability, and consistent mechanical strength. VFDT7 (Ac-Di-Sol-based) exhibited the highest cumulative drug release at 300 seconds. Overall, VFDT6 was identified as the most promising candidate for further development, combining rapid onset, physical robustness, and formulation stability.